How does pain influence cervical endurance test performance in migraine patients? - Rodrigues , Amanda; Bragatto , Marcela Mendes; Florencio , Lidiane Lima; Bigal, Luisa; Bigal, Marcelo; Bevilaqua-Grossi, Débora (Headache Medicine, 2022)
Introduction Migraine sufferers frequently complain of cervical pain during and in-between migraine attacks and studies suggest that chronic neck pain is a risk factor for high-frequency migraine, including chronic migraine. Increased headache frequency and chronic neck pain are, in turn, independently associated with cephalic cutaneous allodynia, a known risk factor for increased headache frequency. Objective To verify the influence that pain in migraine patients has on muscle performace during the cervical endurance test and whether the change in performance is due to pain during the test, neck muscle dysfunction or both. Methods Were evaluate 100 women stratified by diagnosis (migraine, cervical pain, both and none) and self-reported pain during the cervical muscle endurance test in flexion and extension (with or without headache and / or cervical pain during the endurance test). Pain during the test by numerical rate scale (NPRS, 0-10) and pain pressure threshold were collected for all groups. Migraine patients answered 12-item Allodynia Symptom. We used one-way analysis of variance with the Tukey’s HSD post hoc test analysis to contrast pressure pain threshold and endurance across groups. Differences in flexion and extension times were compared using the Welch T-test and the McNemar Test was used to compare differences in headache and neck pain incidence per study group during flexion and extension endurance tests. Results There are significantly differences in mean endurance during flexion between migraine and neck pain [34.4s (25)] relative to neck pain alone [45.2 (18)], migraine [40.2s (29)] and controls [57.5.4s (40)] (p = 0.04). On average, those who experienced headache during the flexion test sustained for significantly less time than those without headache during the test (27.80 versus 46.18 seconds, p<0.01); (To see the complete abstract, please, check out the PDF).